Preoperative clinical management of patients who are candidates for facial transplantation - Martin Iglesias Morales; Mateus de Sousa Borges; Mario Roberto Tavares Cardoso de Albuquerque; Rodolfo Costa Lobato (Revista Brasileira de Cirurgia Plástica)
Introduction: Face transplantation has gained recognition, changing the clinicalsurgical scenario for restoring complex facial defects, as it attributes functional and aesthetic recovery to patients who have suffered serious accidents. At the time of writing this article, in official publications, 43 patients had already undergone facial transplantation worldwide. Face transplantation has numerous pieces of evidence that can irrefutably provide improvements to the patient. For this, preoperative care for the patient must be carefully established so that there is good surgical performance. Case Report: Male patient, 46 years old, reports that, at the age of 6, he had burns due to exposure to gasoline, with 72% of his body surface burned, showing sequelae of burns and surgical reconstructions on the face, with redundant and ptotic skin flap on the left cheek, absence of upper and lower lip and exposure of lower teeth. Conclusion: It is important to publicize this innovative procedure in different medical specialties and preoperative care through a thorough investigation, which attributes better surgical effectiveness, allowing the rescue of their facial identity, once stigmatized.